RETAINED EARNINGS AND FINANCIAL PERFORMANCE OF QUOTED FIRMS IN NIGERIA: AN EMPIRICAL ANALYSIS - Ogunmakin Adeduro Adesola; Bamidele Vincent Olawale; Ogundipe Francis Bamidele (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study examines the impact of retained earnings on the financial performance of listed manufacturing companies in Nigeria. An ex post facto research design was utilized, employing panel data derived from the annual reports of ten (10) companies within conglomerates and consumer goods sectors over a five (5) year period (2019-2023). The research population consists of all 153 manufacturing enterprises listed in the Nigerian Exchange Group as of December 31, 2023. Purposive sampling technique was utilized to determine our sample size. This study utilized descriptive and inferential analysis methods. The descriptive analysis indicated that all variables are normally distributed and suitable for this investigation. Conversely, the inferential analytic methods utilized include Pearson’s correlation analysis, Granger causality analysis, and panel fully modified least squares (FMOLS). The Granger causality test indicates a directional causal link among ROA, RE, and FZ. The outcome demonstrates a directional causal relationship between RE and ROA, with a p-value of 0.5131. The results indicate that ROA does not predict the future value of RE, with a p-value of 0.7431, which exceeds 0.05. The study also reveals a directional causal link between FZ and ROA with a p-value of 0.9019. The findings also suggest that ROA does not forecast the future value of FZ at a p-value of 0.4629, which is greater than 0.05. Furthermore, the data reveals a directional causal link between FZ and RE with a p-value of 0.9571. However, the findings reveal that RE considerably enhances the prediction of the future value of FZ at a p-value of 0.0160, which is less than 0.05. The outcome of the Panel Fully Modified Least Square (FMOLS) shows that retained earnings have no significant link with the return on assets of the quoted firms, with RE having a coefficient of -0.095 and a t-statistic of -0.574 with a p-value of 0.570, which is greater than the 5% threshold of significance.  Furthermore, the result of the Kao integration test shows a p-value of 0.2791 for the Kao residual cointegration test, which is greater than 0.05.  The study concludes that there is no significant relationship between retained earnings and the financial performance of the quoted firms.